2010
DOI: 10.1098/rsbl.2010.0775
|View full text |Cite
|
Sign up to set email alerts
|

Odour-based natal nest recognition in the zebra finch (Taeniopygia guttata), a colony-breeding songbird

Abstract: Passerine birds have an extensive repertoire of olfactory receptor genes. However, the circumstances in which passerine birds use olfactory signals are poorly understood. The aim of this study is to investigate whether olfactory cues play a role in natal nest recognition in fledged juvenile passerines. The natal nest provides fledglings with a safe place for sleeping and parental food provisioning. There is a particular demand in colony-breeding birds for fledglings to be able to identify their nests because m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 23 publications
2
54
0
1
Order By: Relevance
“…If learning is the underlying mechanism, the acquisition of the nest odour might occur pre-hatching [27] or shortly after hatching [20,28], as is known from other bird species. Nevertheless, if the ability of zebra finches to distinguish the two nest odours results from olfactory imprinting, the sensitive phase during which the olfactory template is acquired is much earlier in life than for visual [21,29] and acoustic cues [13,21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If learning is the underlying mechanism, the acquisition of the nest odour might occur pre-hatching [27] or shortly after hatching [20,28], as is known from other bird species. Nevertheless, if the ability of zebra finches to distinguish the two nest odours results from olfactory imprinting, the sensitive phase during which the olfactory template is acquired is much earlier in life than for visual [21,29] and acoustic cues [13,21].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals were tested for 10 min in total. To control for side preferences, we switched odour samples after 5 min [20]. The two stimuli differed in their genetic source and time of exposure to the two test individuals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the intra-specific level, they are known to emit chemical compounds, which are important in several aspects of avian life histories (Caro & Balthazart 2010). For example, birds can recognize their nest using chemical cues (Mínguez 1997, O'Dwyer et al 2008, Bonadonna & Bretagnolle 2002, Bonadonna et al 2003a,b, 2004, de León et al 2003, Caspers & Krause 2011 and they are able to discriminate the scent of their partners from the scent of other conspecifics (Bonadonna & Nevitt 2004, Jouventin et al 2007. Therefore, chemical cues may play a role in social behaviour (Hagelin 2007).…”
mentioning
confidence: 99%
“…Water shrews, another semi-aquatic mammal, preferentially use their olfactory system to detect their prey underwater (Catania et al 2008). Similarly, the birds' sense of smell was long thought to be poor on the basis of anatomical findings (Bang & Cobb 1968, Welty 1975, but behavioral studies have demonstrated that several species of birds possess highly sensitive olfactory systems (Benvenuti et al 1977, Caspers & Tobias 2011, Amo et al 2012. Similarly, it has been found that the number of olfactory receptor genes is not a reliable predictor for an animal's olfactory capacity.…”
Section: Olfactory Discrimination Ability Of Fur Sealsmentioning
confidence: 99%